2018
DOI: 10.1016/j.bmcl.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Design of novel lipidated peptidomimetic conjugates for targeting EGFR heterodimerization in HER2 + cancer

Abstract: The human epidermal growth factor receptor (EGFR) family is known to be involved in cell signaling pathways. The extracellular domain of EGFR consists of four domains, of which domain II and domain IV are known to be involved in the dimerization process. Overexpression of these receptors is known to play a significant role in heterodimerization of these receptors leading to the development of cancer. We have designed peptidomimetic molecules to inhibit the EGFR heterodimerization interaction that have shown an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Furthermore, free Dox showed lower cell viability ( Table 2 ). The results showed that the inclusion of SA-5 as a ligand also played a role in the anti-tumor effect of SA-5-Dox-LP formulation since SA-5 has antiproliferative activity as described in our earlier report [ 15 ]. Additionally, SA-5-Dox-LP showed lower cellular toxicity toward human lung fibroblast cells (HLFs), indicating the non-selective nature of ligand-functionalized liposome for non-cancerous cells that do not overexpress the HER2 protein.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Furthermore, free Dox showed lower cell viability ( Table 2 ). The results showed that the inclusion of SA-5 as a ligand also played a role in the anti-tumor effect of SA-5-Dox-LP formulation since SA-5 has antiproliferative activity as described in our earlier report [ 15 ]. Additionally, SA-5-Dox-LP showed lower cellular toxicity toward human lung fibroblast cells (HLFs), indicating the non-selective nature of ligand-functionalized liposome for non-cancerous cells that do not overexpress the HER2 protein.…”
Section: Resultssupporting
confidence: 69%
“…Compound 5 and lipid conjugate of 5 (SA-5) were known to bind to the HER2 protein and inhibit EGFR dimerization in cancer cell lines [ 15 , 19 ]. SA-5 and SA-5-Dox-LP were evaluated for their ability to inhibit EGFR heterodimerization (protein-protein interactions) in vivo sample tissues of the lungs of mice treated with these formulations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This conjugate accumulated in HER2-overexpressing cell lines and was observed to inhibit protein-protein interactions in vitro via a PLA assay. These peptidomimetics were also conjugated with fluorophores and doxorubicin to target the EGFR related cancer [ 161 , 162 ].…”
Section: Targeting Egfr and Vegfr For Molecular Imagingmentioning
confidence: 99%